English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-31 04:20:28 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

7w(2w-3)(2w+3)
=7w(4w^2 - 9)
=28w^3 - 63w

2007-10-31 04:28:58 · answer #1 · answered by norman 7 · 0 0

try the foil method
foil= first, outside, inside, last

first=2w*2w=4w^2
outside2w*3=6w
inside -3*2w=-6w
last= -3*3=-9

you end up with 7w*(4w^2-9) because -6w and 6w=0

Final answer is then 28w^3-63w

2007-10-31 12:24:12 · answer #2 · answered by cody s 2 · 1 0

fedest.com, questions and answers